Оценка состояния электронных краеведческих ресурсов региональных и муниципальных библиотек (Библиосфера, 2011)
The results of the pilot research for study of local lore electronic resources after the example of The Kemerovo regional libraries are presented. The article considers the main issues of accounting for study of local lore electronic resources.